Assessment and student participation: 'choice and voice' in school principal accounts of schooling territories. Issue 3 (3rd July 2019) - Charteris, Jennifer; Smardon, Dianne
Abstract: Schooling territories are bounded spaces where policies, bodies, practices, and discourses meet and collide. It is well documented in assessment literature that students who are active decision-makers understand their learning processes and have the necessary wherewithal to access support across schooling spaces. These spaces are co-produced through interrelationships, where youth participation is associated with power, voice, democratic citizenship, legal entitlement, empowerment, motivation and self-confidence. Recognising the growing pedagogical emphasis on locating students as responsible for their own learning, we consider how assessment practices constitute enabling and constraining schooling territories. Assessment for learning (AfL) can be linked with emancipatory practices in schooling territories where learner agency is co-produced through socio-material classroom relations. We use principal comments to map a range of interrelated schooling territories as a relational cartography of spatialised practices and student participation in AfL. Mostly, these territories are teacher imagined and defined, constructed through schooling and policy frameworks, and determined through the use of student achievement and student voice data. These conceptualised schooling spaces are interrogated to consider the positionality of students within AfL-related territories. While choice and participation may seem emancipatory, we reveal that AfL practices can serve a rarely acknowledged process of affirming territorial power.